Evaluasi Pelaksanaan Perencanaan dan Pengendalian Jadwal Menggunakan Indikator Percent Plan Complete pada Proyek Gedung Olahraga di Cibubur - Mutia Floresa Wea; Anisah; Muhammad Iqbal (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
On-time completion is a key indicator of success in construction projects. However, in practice, many projects experience schedule deviations due to ineffective planning and unanticipated site constraints. This study aims to evaluate the implementation of planning and schedule control systems on the Sports Hall Project in Cibubur using the Percent Plan Complete (PPC) indicator as a time control tool, and to identify the factors that enabled the project to stay on schedule despite the PPC value not reaching the ideal target.This research uses a descriptive quantitative approach through the analysis of weekly PPC values, schedule deviations, and causes of delay (Reason for Non-Completion/RNC). The results show that the average PPC value only reached 19%, with significant fluctuations throughout the execution period. Although many activities experienced start and finish delays, the actual duration was shorter than planned, indicating acceleration strategies such as overtime and additional labor. The evaluation also revealed that the main constraints were delays in shop drawings, material procurement, and administrative issues.These findings indicate that despite the low PPC value, the project was still completed on time due to the project team’s adaptive responses carried out systematically and collaboratively. Therefore, PPC proves to be an effective evaluative tool for measuring the reliability of planning and the timeliness of project execution